Anatomical Revelations in 1921 Kindled Operative Repair of the Orbit, Eyelids, and Periorbit over the Ensuing 100 Years: The Diuturnity of Ernest Whitnall (1876–1950) of Oxford, Montreal, and Bristol. Issue 2 (June 2019) - Pollock, Richard A.; Gossman, M.Douglas
Revelations of orbital, intraorbital, and periorbital anatomy by a single author in 1921 kindled attempts at operative repair of the orbit, eyelids, and periorbit over the ensuing 100 years. They are the lasting contributions—the diuturnity—of Samuel Ernest Whitnall (1876–1950) of Oxford, Montreal, and Bristol.